TRANSFORMATIONAL LEADERSHIP: A LITERATURE REVIEW - Mochammad Bachtiar Affandie; Sopiah (Bajang Institute, 2022)
Transformational leadership has become the center of attention of researchers and academics and has made it a source of reference or literature on leadership. This literature review is to identify the main points of transformational leadership (TFL) in the last 5 years, namely from 2018-2022. The method used is to search for keywords from the Direct Science and Google Scholar databases. A total of 25 articles of international repute and in English were downloaded. The results of a literature review show that transformational leadership is used as a model in leading that strengthens motivation, stimulates intellect, has charisma and becomes a source of inspiration from leaders to followers